PENTINGNYA PENGGUNAAN ALAT PELINDUNG DIRI BAGI KESEHATAN PETANI DI DESA LOBONG - Tutu, Christien Gloria; Sarman, Sarman; Akbar, Hairil; Mamonto, Faramita; Gunadarma, I Wayan Bennardy (LPPM Institut Pendidikan Nusantara Global, 2022)
Personal protective equipment is one way that workers can use to protect part or all of their body from potential hazards to health and work accidents. Farmers are workers who need PPE when working, especially when handling toxic pesticides. Lobong Village is a village whose people work as farmers who also use pesticides to control plant-disturbing organisms. The application of pesticides without using proper personal protective equipment can increase the risk of pesticide poisoning. With counseling about the importance of using personal protective equipment for farmers, it is hoped that the risk of pesticide poisoning can be minimized so that the health and work productivity of farmers can increase.